2015
DOI: 10.1016/j.schres.2015.08.035
|View full text |Cite
|
Sign up to set email alerts
|

The association of DNA methylation and brain volume in healthy individuals and schizophrenia patients

Abstract: Both methylation and brain volume patterns hold important biological information for the development and prognosis of schizophrenia (SZ). A combined study to probe the association between them provides a new perspective to understanding SZ. Genomic methylation of peripheral blood and regional brain volumes derived from magnate resonance imaging were analyzed using parallel independent component analyses in this study. Nine methylation components and five brain volumetric components were extracted for 94 SZ pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 54 publications
(56 reference statements)
1
29
0
Order By: Relevance
“…Specifically, Horvarth et al was able to find a correlation of around r = 0.9 across the 2 tissues (Horvath et al, 2012), and DNA methylation changes in ten genes identified in the brain of schizophrenic and BD patients have also been confirmed in peripheral blood samples (Xiao et al, 2014). In addition, methylation in peripheral blood has been correlated with brain volume in healthy individuals and schizophrenia patients (Liu et al, 2015), and it has also been correlated with symptoms of major psychiatric disorders, including schizophrenia, depression and BD (Liu et al, 2014; Sabunciyan et al, 2015). …”
Section: Perspectivesmentioning
confidence: 99%
“…Specifically, Horvarth et al was able to find a correlation of around r = 0.9 across the 2 tissues (Horvath et al, 2012), and DNA methylation changes in ten genes identified in the brain of schizophrenic and BD patients have also been confirmed in peripheral blood samples (Xiao et al, 2014). In addition, methylation in peripheral blood has been correlated with brain volume in healthy individuals and schizophrenia patients (Liu et al, 2015), and it has also been correlated with symptoms of major psychiatric disorders, including schizophrenia, depression and BD (Liu et al, 2014; Sabunciyan et al, 2015). …”
Section: Perspectivesmentioning
confidence: 99%
“…Crucially, while initial reports have demonstrated that although DNA methylation patterns are largely tissue-specific, often differing between blood and brain [20,21], there are also similarities [22] and blood DNA methylation shows promise as a biomarker for brain-related traits, including neuropsychiatric disorders [23][24][25][26][27], cognitive ability [28,29] and future psychopathology [26]. However, only a few studies of small sample sizes have reported associations between blood DNA methylation and brain phenotypes [26,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…We identified 2120 such associations from the ICD-9 analyses and 31 associations from the clinical lab analyses where the results are filtered at P-value of 0.001. Among the most significant associations is a novel association between the gene PTGS2 (Prostaglandin-Endoperoxide Synthase 2) and ICD-9 493.20 (chronic obstructive asthma) with P-value = 4.90e − 08 and also between the gene ADRA1D and ICD9-9 780.93 (memory loss) with P-value = 7.64e − 07, where the gene ADRA1D is already known to be associated with Schizophrenia 47 . All Bonferroni significant results in this category are shown in Supplementary Table 1 .…”
Section: Resultsmentioning
confidence: 99%